Campaign management of PT. Foxi Komunika Indonesia Wins in Susilo Bambang Yudhoyono - Boediono on Election 2009 Media Studies A Television Ad - Andi Banus (KOM & REALITAS SOSIAL, 2011)
This paper discusses the 2009 presidential elections won by the incumbent candidate Susilo Bambang Budiyono (SBY) with his partner Boediono. In addition to performance factors that result in the popularity of candidate need for good management, especially on political advertising campaigns on television by political consultants to maintain or improve the image of the candidate. The political issues that are presented in political advertising should be based on facts and credible sources and constructed in accordance with community expectations. Messages must be positive, the effectiveness can be achieved. Management of the Fox campaign against political advertising SBY Indonesia, can maintain popularity and raised the image and reputation of presidential candidate and his running mate, in addition to other factors that influence on political advertising during elections so that SBY-Boediono was elected President and Vice President 2009 period -2014. Political advertising on television as an